Bone regeneration materials and their application over 20 years: A bibliometric study and systematic review - Zhang, Xudong; Li, Qianming; Wang, Zhengxi; Zhou, Wei; Zhang, Linlin; Liu, Yingsheng; Xu, Ze; Li, Zheng; Zhu, Chen; Zhang, Xianzuo (Frontiers in Bioengineering and Biotechnology, 2022)
Bone regeneration materials (BRMs) are considered to be the key to identifying and implement diverse treatments for various types of bone defects. In recent years, material science developments and breakthroughs in tissue engineering technology have resulted in significant progress within the BRM research. The aim of this study was to comprehensively assess the existing research and recent progress on BRMs, thus providing useful insights into contemporary research, as well as to explore potential future directions within the scope of bone regeneration therapy. A comprehensive literature review using formal data mining procedures was performed to explore the global trends of selected areas of research for the past 20 years. The study applied bibliometric methods and knowledge visualization techniques to identify and investigate publications based on the publication year (between 2002 and 2021), document type, language, country, institution, author, journal, keywords, and citation number. The most productive countries were China, United States, and Italy. The most prolific journal in the BRM field was Acta Biomaterialia, closely followed by Biomaterials. Moreover, recent investigations have been focused on extracellular matrices (ECMs) (370 publications), hydrogel materials (286 publications), and drug delivery systems (220 publications). Research hotspots related to BRMs and extracellular matrices from 2002 to 2011 were growth factor, bone morphogenetic protein (BMP)-2, and mesenchymal stem cell (MSC), whereas after 2012 were composite scaffolds. Between 2002 and 2011, studies related to BRMs and hydrogels were focused on BMP-2, in vivo, and in vitro investigations, whereas it turned to the exploration of MSCs, mechanical properties, and osteogenic differentiation after 2012. Research hotspots related to BRM and drug delivery were fibroblast growth factor, mesoporous materials, and controlled release during 2002–2011, and electrospinning, antibacterial activity, and in vitro bioactivity after 2012. Overall, composite scaffolds, 3D printing technology, and antibacterial activity were found to have an important intersection within BRM investigations, representing relevant research fields for the future. Taken together, this extensive analysis highlights the existing literature and findings that advance scientific insights into bone tissue engineering and its subsequent applications.